Genetic Technology Transfer to Kenyan Agriculture in the Context of Biotechnology Research - Andrzejczak, Katarzyna; Przysiecka, Łucja (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
Technology development is a crucial issue for economic development in Sub-Saharan African countries. In this paper current research on biotechnology and the potential of biotechnology absorption in Kenya is analyzed. The institutional character, areas of research and funding mechanisms of the research institutions contributing to agriculture sector technological advancements were examined in the context of local farmer’s needs. Also factors, such as legal framework and cultural and social values for the biotechnology research in the region were explored. Literature review and the qualitative analysis of data on research facilities and the papers from the region were applied in the research. OLS correlation method was applied in the analysis of the data.